1987
DOI: 10.2508/chikusan.58.698
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Milk Constituents by the Near Infrared Spectrophotometric Method

Abstract: A near infrared spectrophotometric (NIR) method was examined to confirm its applicability for measuring the major constituents in raw milk.The samples tested were collected at the National Institute of Animal Industry.The reference methods used were official analytical methods (Gerber,macro-Kjeldahl, Lane-Eynon and the standard gravimetric method) ,and the NIR instrument used was a Model 6350 (Neotec

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The results were comparable with or superior to previously reported direct casein measurements by IR methods. 8,9 Casein, being a protein, is expected to have peaks around 1650, 1550 and 1250 cm 21 due to amide I, amide II and amide III, bands respectively. 10 A spectrum of casein taken as a potassium bromide pellet 11 shows the three distinct amide bands and another strong band in the region 2900-3000 cm 21 , due to C-H stretching.…”
Section: Resultsmentioning
confidence: 99%
“…The results were comparable with or superior to previously reported direct casein measurements by IR methods. 8,9 Casein, being a protein, is expected to have peaks around 1650, 1550 and 1250 cm 21 due to amide I, amide II and amide III, bands respectively. 10 A spectrum of casein taken as a potassium bromide pellet 11 shows the three distinct amide bands and another strong band in the region 2900-3000 cm 21 , due to C-H stretching.…”
Section: Resultsmentioning
confidence: 99%
“…rapidity, non-destructive sample analysis and, especially, a great potential for on-line analysis (RU & gLATZ, 2000;ALBANELL et al, 2003). FT NIR method has been used to measure the content of various constituents in homogenised cow milk (SATO et al, 1987;RODRIgUEZ-OTERO, HERMIDA & CENTENO, 1997;RU & gLATZ, 2000;ŠAŠIČ & OZAKI, 2001). A few authors have reported analysis of non-homogenised milk samples (CHEN, IyO & KAWANO, 1999;LAPORTE & PAQUIN, 1999).…”
mentioning
confidence: 99%
“…Milk has been taken up as the first example because NIR spectroscopy has recently been used for quantitative analysis and quality eva l u ation of milk [22,25]. Chemometrics has been e m p l oyed for the ab ove purp o s e s , but so far there is no report about detailed NIR spectral analysis of milk.…”
Section: Two-dimensional (2d) Correlation Analysis Hasmentioning
confidence: 99%